Stability and economic freedom in the countries of Central and Eastern Europe: Quantitative analysis - Karateev, Artem (Eastern Review, 2019)
Exploring the stability of states and political systems is of interest to scientists and politicians all around the world. One of the most important questions in this field is the question of the relationship between stability and freedom.This paper considers the relationship between economic freedom and stability with regards to the example of countries of Central and Eastern Europe. The study uses quantitative analysis and the operationalisation of economic freedom through the Index of Economic Freedom (IEF); furthermore, stability is studied through the Fragile States Index (FSI), and the Political Stability and Absence of Violence/Terrorism Index (PSI).The analysis reveals a strong correlation between economic freedom and stability. According to linear regression models obtained by the author, economic freedom has a strong impact on stability. Models show that most of the components of IEF increase stability, whilst some components decrease it. This means that the same factors affect economic freedom and stability in different ways. In particular, taxes have a very positive effect on stability. At the same it is obvious that taxes reduce economic freedom. This fact allows us to resolve the existing contradictions among politicians and scientists, who differently assess the impact of economic freedom on stability. It may be stated that whilst economic freedom has in general a strong positive effect on stability, it can also have a negative effect.